Strategic Management of Arabic Language Learning Programs/ إدارة استراتيجية برنامج تعليم اللغة العربية - Amrullah, Abdul Malik Karim; Nida, Zahrotun; Al Anshory, Abdul Muntaqim (Ijaz Arabi Journal of Arabic Learning, 2021)
This research aims to describe the strategic management at the language institute of Hasyim Ay’ari University Jombang, Indonesia to improve students' Arabic language competence starting from the formulation stage, implementation and evaluation. A qualitative descriptive approach as an alternative to this research method, with data collection techniques through interviews, observation and documentation study. From the research it can be concluded that the language institute of Hasyim Ay’ari University Jombang has used good strategic management. This can be seen from the strategy formulation that has been proven by the existence of a strategy formulation composed of a vision, mission and environmental analysis which is then applied into a strategy. Second, the implementation of strategies in the form of several programs and activities that are compiled by the curriculum and tailored to the needs of students. Third, strategy evaluation is carried out using two techniques, namely the program evaluation technique and results evaluation. The final result of this evaluation aims to determine the effectiveness of a program that has been designed and implemented in order to improve student competence. And problems that occur can be found in several aspects, including: administration, infrastructure, accommodation and teaching staff. Which causes less optimal and even not implementing several programs.